Pathology gradual assessment of colorectal anastomosis - A. V. Klymenko; V. M. Klymenko; I. Ye. Kononenko (Patologìâ)
Aim: to analyze the state of the colorectal anastomosis after laparoscopic and open resection of the sigmoid and rectum in patients with colorectal cancer and to develop a unified grading of pathological changes in the anastomosis during its laparoscopic and videorectoscopic assessment.